Peluang Redefinisi Kewenangan Pembentukan Perppu dalam RUU Lembaga Kepresidenan - Rahadian Diffaul Barraq Suwartono (Fakultas Hukum Universitas Islam Indonesia, 2025)
The President's authority to form a Government Regulation in Lieu of Laws, as stated in Article 22 of the 1945 Constitution of the Republic of Indonesia, has recently received more and more criticism and academic review. Recent research shows that a redefinition is needed, or at least a limitation on the scope of